Effectiveness and usage of written and verbal counselling information on anxiety in MRI at a tertiary care hospital in Chennai - Kannapan, Harish; Subhashini; Lakshmi, Abhishri (Journal of Applied Pharmaceutical Research, 2024)
Background: Many people have considerable anxiety when having magnetic resonance imaging (MRI). Fear during an MRI causes the process to drag on longer and the quality of the images to decline, which increases expenses and requires labor loss. Objective: This study sought to determine how vocal and written information affected patients' anxiety during MRI procedures. Materials and Methods: A prospective cross-sectional study with 300 participants was conducted. The investigation occurred in March and April of 2022 at the tertiary care hospital's radiology department. Three participant groups were formed: group 1 received textual material, group 2 served as the control group, and so on; and group 3 learned about counseling. The State-Trait Anxiety Inventory (STAI), a measure of anxiety levels, was used to determine the people's traits and state of anxiety. Results: The three groups' trait anxiety scores did not significantly differ (p = 0.20) from each other's demographic features. Statistically speaking, group 3's state anxiety levels were lower than those of group 2 and the control group. Group 2's state anxiety levels were statistically lower (p<0.001) than those of the control group. Conclusion:Verbal and written information can help to lessen MRI anxiety. Written information may not be as good at lowering MRI anxiety as verbal information.